Accelerated Isothermal Phase Transformation and Enhanced Mechanical Properties of Railway Wheel Steel: The Significant Role of Pre‐Existing Bainite. Issue 2 (27th October 2021) - Gao, Bo; Tan, Zhunli; Tian, Yu; Liu, Yanru; Wang, Rui; Gao, Guhui; Wang, Jiong; Zhang, Min
Abstract : Exploring possible ways to accelerate bainite transformation kinetics and enhance mechanical properties, especially for large‐scale parts, attracted much attention both in industrial manufacturing and fundamental research. Herein, prior continuous cooling transformed bainite is introduced to promote isothermal transformation and improve strength toughness matching of bainite railway wheel steel. Phase transformation study by dilatometer indicates that the time–temperature–transformation curves of tested steel swing back at lower isothermal temperature. This acceleration effect is due to the formation of leaf‐shaped bainite at initial isothermal transformation stage. By tailoring the cooling rate, leaf‐shaped bainite can also be obtained during continuous cooling. It is confirmed that the formation of leaf‐shaped bainite during continuous cooling stage accelerates the subsequently isothermal bainite transformation. In situ microstructure evolution observation demonstrates that prior bainite/ austenite interface provides favorable nucleation site for initial isothermal bainite transformation. Moreover, pre‐existing bainite formed during continuous cooling stage can effectively divide the original austenite grain size. Concurrent enhancement of tensile strength and impact toughness in bainite wheel steel can be achieved by controlling the cooling rate. Abstract : The pre‐existing leaf‐shaped bainite formed during continuous cooling process accelerates the subsequent isothermal bainite transformation kinetics. Newly formed prior bainite/austenite interfaces provide potential nucleation sites for initial isothermal bainite transformation. The existence of prior leaf‐shaped bainite can effectively divide the original austenite grain size, and thus to enhance both tensile strength and impact energy of bainite wheel steel.